1993
DOI: 10.1080/02626669309492678
|View full text |Cite
|
Sign up to set email alerts
|

In situbioremediation of trichloroethylene-contaminated water by a resting-cell methanotrophic microbial filter

Abstract: An in situ microbial filter technology is being tested and developed for remediating migrating subsurface plumes contaminated with low concentrations of trichloroethylene (TCE). The current focus is the establishment of a replenishable bioactive zone (catalytic filter) along expanding plume boundaries by the injection of a representative methanotrophic bacterium, Methylosinus trichosporium OB3b. This microbial filter strategy has been successfully demonstrated using emplaced, attached resting cells (no methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…Effects of cell surface heterogeneity [Simoni et al, 1998] and motile/ nonmotile cells [Camesano and Logan, 1998] on cell attachment in column studies have been recently reported. Studies of microbial attachment in a two-dimensional (2-D) miniature sand-filled aquifer simulator [Shonnard et al, 1994] and a biofilter [Taylor et al, 1993] are reported. Harvey et al [1989] have reported field research on the transport of bacteria in a sandy aquifer.…”
Section: Prior Experimental Approachesmentioning
confidence: 99%
“…Effects of cell surface heterogeneity [Simoni et al, 1998] and motile/ nonmotile cells [Camesano and Logan, 1998] on cell attachment in column studies have been recently reported. Studies of microbial attachment in a two-dimensional (2-D) miniature sand-filled aquifer simulator [Shonnard et al, 1994] and a biofilter [Taylor et al, 1993] are reported. Harvey et al [1989] have reported field research on the transport of bacteria in a sandy aquifer.…”
Section: Prior Experimental Approachesmentioning
confidence: 99%
“…The potential feasibility and effectiveness of an attached resting-cell filter strategy over extended periods of time has been demonstrated for degrading tirchloroethene flowing through a saturated homogeneous quartz sand (Oklahoma) by Taylor et al (1993), Shonnard et al(1994), , and Knapp et al(1995). This special method of allowing contaminants to flow through resting state microbial filters is, therefore, a great benefit in the technology.…”
Section: Novel Applicationsmentioning
confidence: 99%
“…In another unique approach, an in-situ microbial filter technology has been developed for remediating subsurface groundwater contaminated with trichloroethylene (Taylor et al 1993, Knapp et al 1995. This new technology eliminates problems associated with the common method of directly pumping a quantity of nutrients into the subsurface to stimulate growth of indigenous microbes.…”
Section: Novel Applicationsmentioning
confidence: 99%
“…These compounds were removed from a combination of air sparging and biodegradation. Taylor et al (1993) conducted research on the use of a resting-cell (Le., non-dividing) methanotrophic microbial fdter (biofilter) for remediating migrating subsurface plumes of trichloroethylene (TCE). In this system, methanotrophic microorganisms (Methylosinus trichosporium) were injected into a test bed ahead of an migrating TCE plume.…”
Section: Section 3 Literature Reviewmentioning
confidence: 99%